Identification of distinct ChAT+ neurons and activity-dependent control of postnatal SVZ neurogenesis. - Páez-González, Patricia; Asrican, Brent; Rodriguez, Erica; Kuo, Chay T. (Springer Nature, 2014)
Postnatal and adult subventricular zone (SVZ) neurogenesis is believed to be primarily controlled by neural stem cell (NSC)-intrinsic mechanisms, interacting with extracellular and niche-driven cues. Although behavioral experiments and disease states have suggested possibilities for higher level inputs, it is unknown whether neural activity patterns from discrete circuits can directly regulate SVZ neurogenesis. We identified a previously unknown population of choline acetyltransferase (ChAT)+ neurons residing in the rodent SVZ neurogenic niche. These neurons showed morphological and functional differences from neighboring striatal counterparts and released acetylcholine locally in an activity-dependent fashion. Optogenetic inhibition and stimulation of subependymal ChAT+ neurons in vivo indicated that they were necessary and sufficient to control neurogenic proliferation. Furthermore, whole-cell recordings and biochemical experiments revealed direct SVZ NSC responses to local acetylcholine release, synergizing with fibroblast growth factor receptor activation to increase neuroblast production. These results reveal an unknown gateway connecting SVZ neurogenesis to neuronal activity-dependent control and suggest possibilities for modulating neuroregenerative capacities in health and disease.
https://openpolicyfinder.jisc.ac.uk/id/publication/4008
Keywords: Neurobiología del desarrollo; ChAT; SVZ; Neurogenesis